2018
DOI: 10.1136/postgradmedj-2017-135352
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted compared with conventional total hip arthroplasty: systematic review and meta-analysis

Abstract: BackgroundRobotic-assisted total hip arthroplasty (THA) allows for accurate preoperative planning and component positioning, potentially enhancing implant survival and long-term outcomes. The relative efficacy and safety of robotic-assisted and conventional THA, however, are unclear. This systematic review and meta-analysis compared the safety and efficacy of robotic-assisted and conventional THA.MethodsMedline, Embase and the Cochrane Library were comprehensively searched in September 2017 to identify studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 39 publications
1
95
1
Order By: Relevance
“…Also, we contacted experts in the field resulting in one more article eligible for inclusion. As a result, we included 42 SRs 12–14 36–74…”
Section: Resultsmentioning
confidence: 99%
“…Also, we contacted experts in the field resulting in one more article eligible for inclusion. As a result, we included 42 SRs 12–14 36–74…”
Section: Resultsmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is an effective surgery alternative for patients with hip osteoarthritis (OA) or femoral head necrosis [ 1 , 2 ]. Kurtz et al [ 3 ] reported a 50% increase in the prevalence of THA from 1990 to 2002 and estimated nearly 572,000 THAs in 2030.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged surgical times in roboticassisted cases have been attributed to learning curves or the placement of navigation pins and registration. 34 Notably, robotic assistance was used by only two, experienced posterior THA surgeons as the preferred method of instrumentation and it was not available for the majority of the study period (2013-2018). This effectively minimizes its influence on outcomes in this study.…”
Section: Discussionmentioning
confidence: 99%